2003
DOI: 10.1385/mn:28:1:51
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin Response Mediator Proteins (CRMPs): Involvement in Nervous System Development and Adult Neurodegenerative Disorders

Abstract: The members of the collapsin response mediator protein (CRMP) family-five cytosolic phosphoproteins -are highly expressed throughout brain development. The first member to be cloned, CRMP2, was identified as an intracellular messenger required for the growth cone-collapse induced by semaphorin 3A (Sema3A). A rapidly expanding body of study indicates that the functions of CRMPs are not solely limited to the signaling transduction of the Sema3A guidance cue. They are probably involved in multiple cellular and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
214
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(220 citation statements)
references
References 91 publications
3
214
0
3
Order By: Relevance
“…CRMPs are abundant proteins that exist as cytosolic tetramers (14,29,30), of which CRMP2 is the best studied as an essential mediator of growth cone collapse induced by Sema3A signaling (2, 3). CRMP2 itself accumulates in growth cones and also promotes multiple axons when ectopically overexpressed (21,31).…”
Section: Both Crmp1 and Crmp2 Localize To Mitoticmentioning
confidence: 99%
“…CRMPs are abundant proteins that exist as cytosolic tetramers (14,29,30), of which CRMP2 is the best studied as an essential mediator of growth cone collapse induced by Sema3A signaling (2, 3). CRMP2 itself accumulates in growth cones and also promotes multiple axons when ectopically overexpressed (21,31).…”
Section: Both Crmp1 and Crmp2 Localize To Mitoticmentioning
confidence: 99%
“…By applying sequential interaction network filtering, we defined 13 HTT-associated human proteins whose expression in the caudate nucleus of HD patient brains is likely to be abnormal. Evaluation of available data and focused confirmation studies enabled the discovery of the protein collapsin response mediator protein 1 (CRMP1), a neuron-specific phosphoprotein that plays a central role in neuronal development and communication (Charrier et al 2003). Levels of CRMP1 transcription were abnormally low in the brains of HD patients.…”
mentioning
confidence: 99%
“…Among five members of CRMP mammalian homologues (CRMP1-5) 9 , at least CRMP1 and CRMP2 are involved in Sema3A signalling 10 . Mutant mice analysis showed that crmp1 genetically interacts with sema3a in the dendritic and synaptic development of the cortical neurons 11 .…”
mentioning
confidence: 99%